Rancang Bangun Aplikasi Optimasi Penjadwalan Produksi Menggunakan Aturan Prioritas pada PT Remaja Perdana Engineering - Permana, Alvin Indra; Setyawan, Henry Bambang; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Remaja Perdana Engineering is a company engaged in the field of industrial tanks made of steel. The company is located in JL. 224 Sukomanunggal, Surabaya. The products produced by this company are transportation tanks, water tanks and underground tanks that are useful as a media holding.The system is currently used by the company to accept orders is by way of accommodating all orders coming from the customers, and will be scheduled in sequence according to the orders that come in advance which will be scheduled for production. If the company does not have a good scheduling process, companies will experience difficulties in determining the production process come from customers.On the explanation of the above in mind that problems encountered by PT Remaja Perdana Engineering is the process by which it is known that production scheduling system used by the company is not effective, because the waiting time problem impacts on each slot machine. Upon the impact, the company harmed due to the processing of the old product, are at risk of losing customer loyalty, customer will re-think to perform orders if the waiting time is too long. If these problems were not immediately given a solution then the company will suffer losses because the company was forced to reject orders which came due to suboptimal scheduling production owned by the company at this time.Based on problems in the background above, then designed a scheduling optimization of production applications up. The method used is to evaluate the methods included in this priority rule is first come first serve (FCFS), earliest due dates (EDD), Shortest procesing time (SPT), longest processing time (LPT). based on an evaluation of four methods will produce the best method for any period, the evaluation was conducted based on parameters, namely the average resolution time, utilization, number of jobs, the delay in the work.